Knowledge of ICU Nurses Regarding the Ongoing Nursing Assessment of ICU Patients in Khartoum City, 2020 - Ahmed Osman; Montaha Mohammed; Sahar Ahmed (Sudan Journal of Medical Sciences)
Background: An ongoing nursing assessment is the most significant point in the nursing process to be executed in the beginning of every shift which can be accomplished by using different approaches. It needs to be conducted accurately to guide professional nurses’ decision-making ability to further provide holistic nursing care to patients in the intensive care units (ICUs). This study was aimed to assess the ICU nurses’ knowledge regarding ongoing nursing assessment of ICU patients.